Exploring Teacher-Student Talk in Fostering Active Classroom Interaction: A Case Study of EFL Classrooms in Thailand School - Jihan Fadhilah; Henny Mardiah (Universitas Islam Negeri Palopo, 2026)
This study investigates teacher–student talk patterns in fostering active classroom interaction in an EFL context at Islam Wittaya School, Thailand. Using a qualitative case study design, the research examined verbal interactions between one English teacher and 20 third-grade junior high school students through structured classroom observations conducted over four weeks. The data were analyzed using classroom discourse analysis to identify the characteristics of teacher talk, student talk, and overall interactional dynamics. The findings indicate that teacher talk serves as a strategic pedagogical tool through scaffolding, recasts, and adaptive questioning, which gradually shift classroom discourse from teacher-dominated exchanges to more dialogic interaction. Student talk varies across proficiency levels and reflects different engagement patterns shaped by teacher communication strategies. The study shows that effective teacher–student interaction relies on the integration of pedagogical, affective, and socio-cultural factors, including task-based activities, supportive feedback, and peer collaboration, structured teacher talk and scaffolding are designed to foster active student–teacher participation, thereby enhancing students’ communicative competence in classroom interaction.